Transshipments in supply chains: A behavioral investigation (2018)
Behavioral operations studies in inventory management under demand uncertainty have focused on understanding decision-making processes of a single actor. However, interactions among multiple actors have received little attention, despite their importance for the creation of proper policies that improve real operations. We contribute to this literature by experimentally exploring the behavioral biases of retailers’ ordering decisions in a system composed by two symmetric retailers (newsvendors) and an automated supplier, where transshipments between retailers can be used as a strategy to improve the overall supply chain performance. This paper is the first behavioral study that evaluates whether actors coordinate their decisions through transshipment strategies. We analyze the effect of (i) different profitability conditions, (ii) communication and (iii) different behavioral best response heuristics. Results show retailers do not take advantage of transshipments to coordinate the supply chain, and although communication reduces retailers’ ordering biases, coordination does not improve. However, implementing best response heuristics that account for behavioral biases improves supply chain coordination. © 2018 Elsevier B.V.